2021
DOI: 10.21203/rs.3.rs-347764/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Niche differentiation of microbes and their functional signatures in Assam type tea (Camellia sinensis var. assamica)

Abstract: We employed an Illumina-based high throughput metagenomics sequencing approach to unveil the overall rhizospheric as well as endophytic microbial community associated with an organically grown Camellia population located at the Experimental Tea Garden, Assam Agricultural University, Assam (India). Quality control (i.e. adapter trimming and duplicate removal) followed by de novo assembly revealed the tea endophytic metagenome to contain 24,231 contigs (total 7,771,089 base pairs with an average length of 321 bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
0
0
Order By: Relevance
“…Chinese researchers, Xie et al, (2020) and Cakmakci (2019) reported the isolation a p p r o a c h e s a n d t h e d i s t r i b u t i o n o f Methylobacterium in the acidic tea rhizosphere soil. In North India, Bora et al, (2021)…”
Section: Resultsmentioning
confidence: 99%
“…Chinese researchers, Xie et al, (2020) and Cakmakci (2019) reported the isolation a p p r o a c h e s a n d t h e d i s t r i b u t i o n o f Methylobacterium in the acidic tea rhizosphere soil. In North India, Bora et al, (2021)…”
Section: Resultsmentioning
confidence: 99%